Association of workplace stressors with salivary alpha-amylase activity levels among fresh fruit bunch cutters in Selangor - Mohd Nasir, Nur Sabrina; Shamsul Bahri, Mohd Tamrin; Subramanian, Kulanthayan; Shukoor, Nor Shuhada; Zolkifli, Nurzuhairiza; Gin, Siong Ng; Muhamad Akir, Nur Fitriyah; Ananta, Gede Pramudya (Tehran University of Medical Sciences, 2016)
Background: A cross sectional study was conducted to determine the association between occupational stress risk factors and salivary alpha-amylase activity levels among fresh fruit bunch (ffb) cutters at oil palm plantation.